Radical grafting of medium chain-length poly-3-hydroxyalkanoates with glycerol 1,3- diglycerolate diacrylate to form amphiphilic gels: Mechanism and copolymer characterization / Syed Mohammad Daniel Syed Mohamed - Syed Mohammad Daniel , Syed Mohamed (2019)
Radical grafting of medium chain length poly-3-hydroxyalkanoates (mcl-PHA) with glycerol 1,3-diglycerolate diacrylate (GDD) in acetone was successfully carried out using benzoyl peroxide (BPO) as sole micro-initiator. A detail mechanism scheme provides significant improvement to previous literature. Radical-mediated grafting generated a-b carbon inter-linking of mcl-PHA and GDD resulted in macromolecular structure with gel properties. Thermal characterization distinguished the thermal properties of the copolymer for different graft yields as a function of initiator concentration, GDD monomer concentration, incubation period and temperature. The water absorption and porosity of the gel were significantly improved relative to neat mcl-PHA.